Role of the antioxidant defence system and transcription factors in preventing heat stress in poultry: a dietary approach - Şahin, Kazım; Sahin, Emre; Deeh, Patrick B. D.; Kayri, Veysi; Orhan, Cemal; Şahin, Nurhan (Taylor & Francis Ltd, 2023)
The most important stress factors that disrupt homoeostasis, i.e. stable internal balance, in poultry are environmental, nutritional, microbiological, and managing, negatively affecting poultry health and production. Over the past few years, the prevalence of heat stress conditions in poultry production areas worldwide has increased due to climate change. Among the environmental stressors, high ambient temperatures pose a significant challenge to poultry production, resulting in substantial economic losses and molecular and cellular changes that compromise animal health and productivity. High ambient temperature lead to an increase in the production of reactive oxygen species (ROS), causing oxidative stress and damaging the antioxidant capacity of the poultry. Oxidative stress has the potential to harm cell proteins, lipids, and DNA, leading to cellular dysfunction. The amount of reactive oxygen species (ROS) that increase with the effect of heat stress is regulated by the antioxidant defence system together with transcription factors and vitagenes. Activation of vitagenes through transcription factors leads to synthesising various protective molecules that try to prevent ROS overproduction. Nutrients such as vitamins E, and C, selenium, and curcumin play a crucial role in antioxidant processes. When these nutrients are included in the poultry diet, they enhance the antioxidant defence system, thereby combating the detrimental effects of stress factors and improving the immune system's defence. This perspective on improving antioxidant defence for poultry under stress conditions concerns the activation of essential transcription factors such as nuclear factor kappa-B (NF-& kappa;B) and nuclear factor-erythroid-2 related factor 2 (Nrf2). Therefore, the development of nutritional supplements that regulate vitagenes has become a priority for enterprises involved in poultry production. This review focuses on examining the impact of several nutrients on the antioxidant defence system and transcription factors in mitigating heat stress in poultry.
Keywords: Heat stress; nutrition; minerals; vitamins; >